Characterization of hen eggs for the designing of an automatic classification system (2012)
The parameters that define the quality of production in the fowl sector are related to the physical characteristics of the eggs, so the classification process for a producer of eggs is critical, for which reason can cause losses because of egg fractures, weighing errors, excessive times for the process and low accessibility in local technology. In the present work, the physical characteristics of hen eggs are analyzed to define the fracture toughness under static and dynamic conditions as well as the energy parameters for the subsequent design of an automatic classification system for the company called HUEVOS located in Duitama Boyacá. The relationship between weight, egg size, position and the compressive strength of hen eggs was found. The design of an automatic classification system and its control and supervision is presented. There is a direct relationship between the classification for weight and size of hen eggs, but no relationship between egg size and compressive strength was found. The mechanical system designed prevents fractures in healthy eggs and the automatic control system allows easy installation in the proposed design.